Principles of diagnosis and treatment of nodular goiter - T. Y. Demidova; I. N. Drozdova; N. P. Potekhin; F. A. Orlov (Медицинский совет, 2016)
One of the most common diseases of the thyroid gland is nodular goiter. The widespread use of modern diagnostic methods (ultrasound, computed tomography, magnetic resonance imaging) helps to identify a huge number of thyroid incidentalomas. This, in turn, requires clear and clinically substantiated guidelines for the diagnosis and treatment of nodular goiter. Such guidelines are being developed by both Russian and foreign endocrinologists, which are the same across the main provisions but have some differences as well. Advancements in diagnostic methods and accumulation of clinical experience result in a regular update of the recommendations. Examination of patients with nodular goiter focuses on ruling out malignant thyroid. Among nodular abnormalities, thyroid cancer is detected in 4,7--5,0% of cases.